Effect of compatibilizer on the structure and property of polycarbonate/polypropylene alloys. Issue 40 (4th August 2022) - Yu, Xingxing; Ren, Jifu; He, Jingwei; Su, Long; Liu, Fang
Abstract: Polycarbonate/Polypropylene (PC/PP) alloy is a typical thermodynamically incompatible system. In this work, ethylene‐methyl acrylate copolymer (EMA), methoxamine hydrochloride‐grafted POE (POE‐g‐MAH), ethylene‐butyl acrylate‐glycidyl methacrylate copolymer (EAY), a self‐made compatibilizer (PPM‐g‐GMA) of a mixture of glycidyl methacrylate grafted PP (PP‐g‐GMA) and glycidyl methacrylate‐grafted POE (POE‐g‐GMA) were selected as compatibilizer to prepare PC/PP alloys with the mass ratio of 65:30. Systematical studies of compatibilizer type, content and its effects on microstructure, mechanical properties, dielectric properties, dielectric properties and dynamic rheological properties have been carried out in this PC/PP alloys. The results demonstrated that all the compatibilizers in this article resulted in an effective improvement of the compatibility of PC/PP alloys, and the self‐made compatibilizer of PPM‐g‐GMA exhibited a significant improvement over the other three compatibilizers in notched izod impact strength, tensile strength, and bending strength. In addition, a relative low dielectric constants and dielectric losses under 2.5 GHz electric field could be obtained with the assistance of POE‐g‐MAH and PPM‐g‐GMA, indicating its possible application in dielectric materials. Abstract :